Energy Harvesting: Measured Output Voltages of Piezoelectric Devices Depend on the Resistance of Voltmeter (Adv. Funct. Mater. 33/2015). (September 2015) - Su, Yewang; Dagdeviren, Canan; Li, Rui
Abstract : A lead zirconate titanate (PZT) mechanical energy harvester (MEH) enables high efficiency mechanical to electrical energy conversion from the natural contractile and relaxation motion of the heart. On page 5320, Y. Su, C. Dagdeviren, and co‐workers show that the measured voltage of the MEH depends on the inner resistance of the voltmeter, which is contrary to the established knowledge that the measurement results are independent of the instruments used. Cover designed by Zhenhai Li.